The Application of TGFU Learning in Basketball Shooting Learning - Sandy, Ary; Wardiah, Dessy; Junaidi, Ilham Arvan (Journal of Social Work and Science Education, 2023)
Teaching Games for Understanding (TGfU) is an approach to physical education learning to introduce how children understand sports through the basic concepts of play. TGfU does not focus on learning techniques for playing sports so that learning will be more dynamic and in accordance with the child’s developmental stage. Learning physical education is not boring for children through the TGfU approach. To learn shooting techniques in basketball games at school requires the right learning model because shooting basketball exercises using the drill method in learning is boring for students. The purpose of this study was to determine the application of TGFU (Teaching Game for Understanding) learning in basketball shooting learning. The method used in this research is literature review. Here, we will describe the relation to the application of TGFU learning to shooting material in basketball games. With the results of research from various sources, it can be concluded that the application of TGFU learning has a significant effect on shooting basketball.